THE SCHOOL ENROLLMENT OF CHILDREN IN THE PLANTATION SECTOR IN INDONESIA - NFN Ngadi (Jurnal Kependudukan Indonesia, 2016)
This paper aims to analyze the determinants of school enrollment of children age 10–15 whose parents are working in plantation sector, Indonesia. The data for the analysis is obtained from the 2013 National Socioeconomic Survey conducted by Badan Pusat Statistik, Indonesia. The data covers 20,311 children at age 10–15 in the plantation sector. The analysis is carried out using the descriptive and logistic regression models. The result shows that the enrollment rate for children age 10–15 in the plantation sector was high at 93.7 percent. Meanwhile, the logistic regression analysis shows that the economic activity of children (working or not working) was the most influencing factor on the educational enrollment. Working children had 0,085 times less chance to enroll in education than children who do not work. This finding is compounded by the fact that many heads of household only complete primary schooling. That makes it difficult for working children to enroll in schooling. Therefore, the government should improve the quality of education so that the educational benefit will be greater than the forgone earnings. In addition, it is important to increase the household income in order to prevent children from working.